The Effect Of Service Quality On Inpatient Satisfaction At Syekh Yusuf Regional General Hospital, Gowa Regency - Rini Wijayaningsih; Syamsuriati Syamsuriati; Muamar Asykur (CV. AFDIFAL MAJU BERKAH, 2026)
Globally and nationally, patient satisfaction levels still fall short of SPM standards, especially in government hospitals. The decline in visits and patient satisfaction indicates a gap in healthcare service quality that needs to be addressed. This study aims to analyze the effect of service quality on inpatient satisfaction at Syekh Yusuf Regional Hospital, Gowa Regency. This study used a quantitative method with an observational analytical approach and a cross-sectional design. A total of 135 respondents were selected using purposive sampling. Data were collected through questionnaires and analyzed using chi-square and multiple linear regression. The results showed that all dimensions of service quality (SERVQUAL)—tangibles (p=0.039), reliability (p=0.002), responsiveness (p=0.016), assurance (p=0.000), and empathy (p=0.000)—had a positive and significant effect on patient satisfaction. The most dominant variable influencing patient satisfaction was assurance (β=0.285). Although the quality of inpatient services at Syekh Yusuf Regional Hospital was generally good (43%), improvements are still needed in several service aspects to optimize patient satisfaction and improve the quality of healthcare services.